2020
DOI: 10.1051/0004-6361/202037525
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of photospheric flows under an erupting filament in the quiet-Sun region

Abstract: Context. We studied the dynamics of the solar atmosphere in the region of a large quiet-Sun filament, which erupted on 21 October 2010. The filament eruption started at its northern end and disappeared from the Hα line-core filtergrams line within a few hours. The very fast motions of the northern leg were recorded in ultraviolet light by the Atmospheric Imaging Assembly (AIA) imager. Aims. We aim to study a wide range of available datasets describing the dynamics of the solar atmosphere for five days around t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 34 publications
1
2
0
Order By: Relevance
“…Meanwhile, the fields become nonpotential and energetic (Shimizu et al 2014). As revealed in previous studies, highly twisted (Rust & Kumar 1996;Titov & Démoulin 1999) or sheared (Bobra et al 2008;Roudier et al 2008;Wollmann et al 2020) magnetic flux rope typically suggests strong complexity and nonpotentiality, as well as more free magnetic energy of the fields (Yamada et al 2010). In this study, the sigmoid-like structure (Rust & Kumar 1996) in Figure 4 magnetic reconnection may be triggered easily in a nonpotential environment.…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…Meanwhile, the fields become nonpotential and energetic (Shimizu et al 2014). As revealed in previous studies, highly twisted (Rust & Kumar 1996;Titov & Démoulin 1999) or sheared (Bobra et al 2008;Roudier et al 2008;Wollmann et al 2020) magnetic flux rope typically suggests strong complexity and nonpotentiality, as well as more free magnetic energy of the fields (Yamada et al 2010). In this study, the sigmoid-like structure (Rust & Kumar 1996) in Figure 4 magnetic reconnection may be triggered easily in a nonpotential environment.…”
Section: Discussionsupporting
confidence: 73%
“…As a result of the horizontal flows, Roudier et al (2008) have revealed an increase in the shear below the point where the filament eruption starts and a decrease in shear after the eruption, and they conclude that the shear pumps the energy to the atmospheric structure. Largescale flows in the direction opposite to the differential rotation can create strong shear along the magnetic polarity inversion line of a filament channel, which influences the stability of the structure and contributes to the eruption of the filament (Roudier et al 2018;Wollmann et al 2020).…”
Section: Discussionmentioning
confidence: 99%
“…For example, the convection cells transport the magnetic field and form a magnetic polarity inversion line between them (Roudier et al 2018a). A previous study shows the importance of the photospheric flows for influencing the stability of the structures of the magnetic field in upper layers of the solar atmosphere (Wollmann et al 2020), for example in the destabilation and eruption of solar filaments.…”
Section: Possible Link Between Donuts and Dynamical Events Of The Sol...mentioning
confidence: 99%